Systematic review of near-infrared spectroscopy determined cerebral oxygenation during non-cardiac surgery - Nielsen, Henning B. (Frontiers in Physiology, 2014)
Near-infrared spectroscopy (NIRS) is used to monitor regional cerebral oxygenation (rScO2) during cardiac surgery but is less established during non-cardiac surgery. This systematic review aimed i) to determine the non-cardiac surgical procedures that provoke a reduction in rScO2 and ii) to evaluate whether an intraoperative reduction in rScO2 influences postoperative outcome. The PubMed and Embase database were searched from inception until April 30, 2013 and inclusion criteria were intraoperative NIRS determined rScO2 in adult patients undergoing non-cardiac surgery. The type of surgery and number of patients included were recorded. There was included 113 articles and evidence suggests that rScO2 is reduced during thoracic surgery involving single lung ventilation, major abdominal surgery, hip surgery, and laparascopic surgery with the patient placed in anti-Tredelenburg’s position. Shoulder arthroscopy in the beach chair and carotid endarterectomy with clamped internal carotid artery also cause pronounced cerebral desaturation. A >20% reduction in rScO2 coincides with indices of regional and global cerebral ischemia during carotid endarterectomy. Following thoracic surgery, major orthopedic and abdominal surgery the occurrence of postoperative cognitive dysfunction might be related to intraoperative cerebral desaturation. In conclusion, certain non-cardiac surgical procedures is associated with an increased risk for the occurrence of regional cerebral oxygenation. Evidence for an association between cerebral desaturation and postoperative outcome parameters other than cognitive dysfunction needs to be established.